ANALISIS KOMPARASI PENGELOLAAN BIAYA PENDIDIKAN SEKOLAH TINGKAT DASAR DI KABUPATEN BOGOR - Siti Alpi Napisah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to determine the financing distribution system in several elementary schools in Bogor Regency and find out the effectiveness and efficiency of managing the costs of some of these schools. The method used is to conduct an analysis by interviewing several respondents concerned regarding the title, also the author uses the literature study method to complete the results of the research that has been carried out. In this study, the object of the study is the percentage of the division of types of costs obtained and used in the management system in the 2022/2023 school year. The results of research from several schools in Bogor Regency, it is known that the source of income for elementary school education costs in Bogor Regency as much as 70% comes from the Government, namely in the form of BOS funds and 30% comes from tuition fees, as well as related school foundation funds. As for the financing that comes out of the research results, some schools generally spend 50% on employee salaries, 30% for the procurement of infrastructure, and 20% for activities held by schools.